2018
DOI: 10.3892/ol.2018.8172
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a promotes cell migration and invasion in melanoma by directly targeting SMAD4

Abstract: Previous studies have explored the functions of microRNA (miR)-146a in different types of cancer through mediating different targets. However, the roles of miR-146a in malignant melanoma (MM) cell migration and invasion remain largely elusive. In the present study, the potential molecular function of miR-146a in MM was investigated. Reverse transcription-quantitative polymerase chain reaction was utilized to detect miR-146a expression in MM tissues and cell lines. A Transwell assay was performed to confirm the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Other investigators confirmed using transwell assays that miR‐146a could also promote malignant melanoma migration and invasion. SMAD4 was targeted by miR‐146a in these cells, and ectopically expressing SMAD4 could block the effects of the miRNA on migration and invasion (Pu et al, ). Overall, miR‐146a can affect multiple signaling pathways in melanoma cells, including Notch and TGF‐β.…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%
“…Other investigators confirmed using transwell assays that miR‐146a could also promote malignant melanoma migration and invasion. SMAD4 was targeted by miR‐146a in these cells, and ectopically expressing SMAD4 could block the effects of the miRNA on migration and invasion (Pu et al, ). Overall, miR‐146a can affect multiple signaling pathways in melanoma cells, including Notch and TGF‐β.…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%
“…It's a part of transforming growth factor-beta (TGF-β) signaling pathway by activating SMAD proteins forming a complex with SMAD4 protein. As a central mediator of TGF-β signaling, SMAD4 plays a role in cell differentiation, migration, invasion, and apoptosis [47]. Mouse models suggest that SMAD-mediated signaling in melanoma can play various functions, such as the proliferation of melanoma cells [48].…”
Section: Smad4mentioning
confidence: 99%
“…In our present study, DEMs analysis found that miR-146a and miR-153b were both more highly detected in TM compared to those in WT. In mammals, recent studies have reported that miR-146a played an important role in melanoma [39,40,41] and retinal pigment epithelial cells [42]. Similarly, miR-153 could suppress cell proliferation and invasion by targeting snail family transcriptional repressor 1 (SNAI1) in melanoma [43].…”
Section: Discussionmentioning
confidence: 99%